(untitled) (Journal of Nepal Geological Society, 2004)
The Bhairahawa-Lumbini Groundwater Irrigation Project (BLGWIP) is the largest groundwater development project of Nepal. It is situated in the middle of the Rupandehi district in west Nepal. The project covers an area of about 525 sq. km and serves over 20,000 ha of land by providing year-round irrigation. Over 180 deep tubewells were constructed by the BLGWIP within the area stretching between the Rohini Rive r in the east and the Kothi River in the west with the depth ranging from 80 to over 200 m. Seven different sections were taken to study the subsurface geology and nature of aquifer in this area. These seven sections include 61 deep tubewells. The lithological cross-sections show the distribution of pervious and impervious layers. The study shows that the aquifer materials are controlled by two major rivers: the Tinau River and Dano River. The lithological cross-sections I- I’ and VII- VII’ are taken from extreme west and east of the study area, respectively. Clay and silt horizons arc predominant in both sections. On the other hand, the remaining cross-sections II- II’, III-III’, I V- IV’, V- V’, and VI- VI’ are taken from the central part of the study area. The litholog of boreholes of these sections show a significant amount of sand and gravel. Most of the deep aquifers recharge from infiltration of rainfall in the Bhabar Zone and also from the induced infiltration through the Tinau, Dano, Rohini, and other rivers flowing through the district. The study shows that the input to groundwater is as high as 464 million cubic metres (MCM). Out of this, 201 MCM goes into the shallow aquifers and 267 MCM flows into the deep aquifers.